PERAN KURIKULUM AKHLAK DALAM PEMBENTUKAN KARAKTER DI SEKOLAH ALAM SOU PARUNG BOGOR - Fatmawati Fatmawati; Yusrizal Yusrizal (JURNAL TEMATIK, 2020)
Education plays an important role in teaching students, education can be found anywhere,especially in schools. School as a place for teaching recipients given by educators to students. This studyaims to determine how important the moral curriculum plays in character building in the SoU ParungBogor natural school. The approach used in this research is a qualitative approach with a descriptivetype. Data collection techniques using observation, interviews and documentation. The results showedthat. 1) The moral curriculum is carried out at any time, morals are the top priority for students of theSoU Parung Bogor natural school; 2) The moral curriculum makes students closer to God, good relationsbetween humans and the environment; 3) the moral curriculum as a determinant in character building inthe SoU Parung Bogor natural school, if the curriculum is implemented properly, the children's characterwill also be well formed.